2017
DOI: 10.1371/journal.pone.0175442
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a diabetes numeracy test in Arabic

Abstract: BackgroundThe prevalence of diabetes Mellitus in Saudi Arabia is 24%, ranking it among the top ten Worldwide. Diabetes education focuses on self-management and relies on numeracy skills. Poor numeracy may go unrecognized and it is important to have an assessment tool in Arabic to measure such a skill in diabetes care.ObjectivesTo validate a 15-item Diabetes Numeracy Test (DNT-15) in the Arabic Language as a tool to assess the numeracy skills of patients with diabetes and to test its properties among Saudi pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…Based on the results, the higher scores on the DNT-15 test showed no statistically significant association with the duration of diabetes. This finding is consistent with the observations of previous studies [45,47]. However, it is possible that the diabetes-specific numeracy skills do not show an explicit connection with the time of diabetes diagnosis, since such skills may be more related to an individual's self-efficacy and self-management behavior [62].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on the results, the higher scores on the DNT-15 test showed no statistically significant association with the duration of diabetes. This finding is consistent with the observations of previous studies [45,47]. However, it is possible that the diabetes-specific numeracy skills do not show an explicit connection with the time of diabetes diagnosis, since such skills may be more related to an individual's self-efficacy and self-management behavior [62].…”
Section: Discussionsupporting
confidence: 91%
“…The number of clinical studies on general HL and numeracy is growing; there are much fewer still (especially in Europe) focusing on patients with specific chronic diseases such as those diagnosed with T2DM and prescribed different insulin regimes. The research by Alghodaier et al (2017) clearly states that the influence of numeracy on the health of patients with diabetes has been investigated in a small number of studies [45]. Based on one meta-analysis it is recommended to invest the assessment of diabetes numeracy to produce more evidence on the relationship with different diabetes outcomes, including self-care activities [11].…”
Section: Diabetes-specific Numeracy Skills and Their Impact On Healthmentioning
confidence: 99%
“…Convergent validity is tested based on the association between a focal measure (the DHNT in this study) and a comparator instrument with which conceptual convergence is expected [40]. As expected, the DHNT exhibited a moderate correlation with diabetes knowledge in the present study, which is consistent with the findings of previous studies [4,41]. The presence of criterion validity implies that a focal measure is consistent with a criterion measuring the same construct [40].…”
Section: Discussionsupporting
confidence: 85%
“…46 Furthermore, patients of our study had a lower mean diabetes numeracy score (41.3%) in comparison to other studied patients. 13,34,37 Saudi patients of another study had a relatively higher mean diabetes numeracy score (53.3%). 34 Also, another study demonstrated that 60% of patients on insulin pump therapy scored 90% and higher on DNT-15 test.…”
Section: Dnt-15 Score and Diabetes Self-managementmentioning
confidence: 90%
“…13,34,37 Saudi patients of another study had a relatively higher mean diabetes numeracy score (53.3%). 34 Also, another study demonstrated that 60% of patients on insulin pump therapy scored 90% and higher on DNT-15 test. 37 Additionally, the patients in our study were found to perform best at addition and subtraction, and worst at multistep mathematics.…”
Section: Dnt-15 Score and Diabetes Self-managementmentioning
confidence: 90%